PERANAN PENDIDIKAN ISLAM DI LINGKUNGAN KELUARGA DALAM PEMBENTUKAN KEPRIBADIAN MUSLIM - Asih, Sri; Wigati, Siti; Sulistiani, Siti Fatima; Habibah, Siti; Romlah, Siti; Astuti, Siam (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study uses a library research method, namely research whose main object is books and other literature as the object of analysis. The primary data source is the interpretation of the Qur'an al-'azim. While the secondary data sources are the interpretation books written by the scholars and supporting books related to the problem being studied. The method used is the maudu'i method, namely thematic method by collecting and compiling all verses or hadiths that have the same direction, then analyzing them from various aspects to then presenting them into a particular theme with the nature of analytical descriptive research. The purpose of the study is to explain and facilitate understanding the meaning of the role of Islamic education in the family environment in the formation of Muslim personality, as well as to increase and expand insight into thinking about the meaning of Islamic education and also the principles of Islamic education. The results of this study indicate that as a consequence of faith, a Muslim should be consistent and consistent in studying, studying and even contemplating the contents of the Qur'an. By studying its contents, we will add to our new treasury, broaden our horizons of thought and knowledge, increase new perspectives and always encounter new things. Furthermore, we will be more convinced of the uniqueness of the contents of the Qur'an which shows the Greatness of Allah as the Almighty Creator. Based on the results of the analysis both textually and contextually on the role of Islamic education in the family environment in the formation of Muslim personality, there are several implications including: the concept of Islamic education in the family environment, the urgency of education in the family environment in the formation of Muslim personality, the implementation of family education in the household in forming Muslim personalities, describing the patterns of application of Islamic education carried out in the family environment, namely in the household in order to realize Muslim personalities, the formation of Muslim personalities in the family environment from the perspective of Islamic education, the concept of informal Islamic education in the family environment, and the last is other verses or arguments concerning the importance of Islamic education to realize ideal personalities according to Islamic teachings